Composite mineral admixture based on iron ore tailing mud and preparation method thereof
By using composite mineral blends based on iron ore tailing mud in cement, the problems of reduced cement strength and high energy consumption are solved, efficient production of cement and environmentally friendly resource recycling are achieved, and the mechanical properties of cement are improved. Durability.
Patent Information
- Application Number
- CN202411305541.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-03
AI Technical Summary
The use of existing mineral blends in cement concrete can easily lead to the reduction of the strength of cement in the early or later stages, and the energy consumption of cement production is high and environmental pollution is serious, making it difficult to achieve green and low-carbon solid waste resources recycling.
Using composite mineral blends based on iron ore tailing sludge, by activating the combination of iron ore tailing sludge, layered ultrafine powder, methacrylic-cellulose copolymer, limestone powder, composite abrasive agent and composite exciter, A composite mineral blend with a high specific surface area is prepared to improve the mechanical properties and durability of cement, and the reactive activity of active oxides is improved through technical means such as ultrasonic treatment and microwave heating.
It significantly increases the amount of cement, reduces cement production costs, improves the density, anti-seepage performance and durability of cement, reduces energy consumption, and achieves the resource recycling and environmental governance goals of iron ore tail mud.
Smart Images

Figure BDA0005049055490000091 
Figure BDA0005049055490000092 
Figure BDA0005049055490000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composite mineral admixture based on iron ore tailings and a preparation method thereof. Background Art
[0002] At present, cement production consumes a lot of energy, and producing one ton of cement produces about one ton of carbon dioxide greenhouse gas. In order to change this situation, various metallurgical slags (slag, steel slag), fly ash, limestone powder, rice husk ash, waste glass powder, etc. are used as admixtures in cement production, or as mineral admixtures in concrete production to reduce the energy consumption of cement production, improve the environment, and improve the durability of cement concrete.
[0003] Composite mineral admixtures refer to two or more powder materials with one or more oxides such as silicon, aluminum, calcium as main components, with specified fineness, and evenly mixed in a certain proportion, which can change the properties of concrete. The existing admixtures mainly play the role of reducing the production cost of cement concrete, and these mineral admixtures are prone to cause early or late strength reduction of cement during use.
[0004] Iron ore tailings are waste after ore dressing and are also the main component of common industrial solid waste. Tailings, sludge, mining waste rock, etc. are clearly listed as key comprehensive utilization areas in the "Hainan Province Bulk Industrial Solid Waste Comprehensive Utilization Development Plan (2022-2025)". In view of this, the harmless treatment and efficient resource utilization of solid wastes such as tailings have become the focus of current scientific research and practice, aiming to promote solid waste management in Hainan Province and even in a wider area towards green, circular and low-carbon directions.
[0005] Therefore, developing a composite mineral admixture using iron ore tailings can not only reduce costs and improve cement performance, but also comprehensively utilize industrial solid waste iron ore tailings to achieve resource recycling and achieve green and low-carbon goals in solid waste management, which is of practical significance. Summary of the invention
[0006] In view of this, the present invention proposes a composite mineral admixture based on iron ore tailings and a preparation method thereof.
[0007] The technical solution of the present invention is achieved in this way:
[0008] A composite mineral admixture based on iron ore tailings comprises the following raw materials in parts by weight: 30-40 parts of activated iron ore tailings, 5-10 parts of layered ultrafine powder, 5-10 parts of methacrylic acid-cellulose copolymer, 5-7 parts of limestone powder, 1-3 parts of composite grinding aids and 1-3 parts of composite activators.
[0009] Furthermore, the particle size of the layered ultrafine powder is 1-10 μm.
[0010] Furthermore, the layered ultrafine powder is obtained by co-ball milling a mixture of montmorillonite, hydrotalcite and pyrophyllite in a mass ratio of 3-5:1-3:1-3 with a titanate coupling agent;
[0011] The mass ratio of the mixture of montmorillonite, hydrotalcite and pyrophyllite to the titanate coupling agent is 1:0.1-0.3.
[0012] Furthermore, the preparation steps of the activated iron ore tailings include: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding, calcining in stages, adding the product to an activation solution, ultrasonically treating, washing and drying to obtain the activated iron ore tailings.
[0013] Furthermore, the total content of Al2O3 and SiO2 in the iron ore tailings is greater than 63%, and the SO3 content is greater than 1.8%; the grinding particle size is 15-25μm; the staged calcination is firstly to increase the temperature to 400-600℃ at a heating rate of 2℃ / min for calcination for 40-60min, and then to increase the temperature to 800-1000℃ at a heating rate of 1℃ / min for calcination for 30-60min; the activation solution is composed of polyvinyl alcohol and acetic acid in a mass ratio of 0.2-0.4:1; the ultrasonic treatment is to ultrasonicate at 100-300rpm and 40-60℃ for 1-2h.
[0014] Furthermore, the preparation step of the methacrylic acid-cellulose copolymer includes: adding cellulose to water and heating and stirring with microwave, adding ammonium sulfate and methacrylic acid in sequence to react for 5-7 hours, dropping sodium hydroxide with a concentration of 0.3-0.4 mol / L, adjusting the pH to neutral, and obtaining the methacrylic acid-cellulose copolymer.
[0015] Furthermore, the solid-liquid ratio of the cellulose and water is 1:10-20 g / mL; the microwave heating and stirring is heated at 400-500 W and 60-80° C. for 30-60 min; and the molar ratio of ammonium sulfate to methacrylic acid to cellulose is 0.08-0.1:1-2:3-5.
[0016] Furthermore, the composite grinding aid is polyvinyl alcohol, triethanolamine and calcium sulfate in a mass ratio of 1:3-5:1-3.
[0017] Furthermore, the composite activator is nano-calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 1:1-3.
[0018] A method for preparing a composite mineral admixture based on iron ore tailings, the specific steps comprising:
[0019] (1) Grind the activated iron ore tailings to a particle size of 20-30 μm, add layered ultrafine powder and 30%-40% of composite grinding aid, and continue grinding until the specific surface area is 400-600 m 2 / kg;
[0020] (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid is added, and the mixture is ground to a specific surface area of 700-900 m 2 / kg;
[0021] (3) Mix the mixture from step (2) and the composite activator evenly and grind until the specific surface area is 1000-1100m 2 / kg, particle size 1-5μm, to obtain the target composite mineral admixture.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The composite mineral admixture of the present invention can maximize its dosage in cement, reduce the amount of cement clinker, and reduce the cost of cement production. The composite cement has better mechanical properties, volume stability and durability. The composite mineral admixture of the present invention has finer particles of 1-5μm and a higher specific surface area of 1000-1100m 2 / kg, effectively filling the tiny gaps between unhydrated cement and hydration products, thereby increasing the density of cement and improving strength. Composite mineral admixtures play a role similar to the "nucleus effect" in the process of cement hydration, increasing the number of hydration products formed, while making the hydration products more evenly distributed in the entire interface transition zone, generating more stable hydration products and improving anti-seepage performance.
[0024] 2. The main minerals of the iron ore tailings of the present invention are quartz, hematite, kaolin, ferrocalcium amphibole, etc., and their high Fe2O3 content can not only react with calcium ions in cement clinker to form calcium iron ore phases such as C4AF with good stability, but also enhance the long-term performance and durability of cement products in harsh environments. Secondly, the iron oxides in the iron ore tailings act as fluxes at high temperatures, which can promote the formation of mineral phases and achieve conversion to admixtures at lower temperatures, significantly reducing energy consumption and reducing production costs. In addition, the quartz, potassium feldspar and silicate minerals rich in the iron ore tailings have more excellent grinding performance due to their high brittleness. The total content of Al2O3 and SiO2 in iron ore tailings is greater than 63%, and the SO3 content is greater than 1.8%, which meets the requirements of GB / T 2847-2022 (volcanic ash mixed materials used in cement). After the iron ore tailings are activated, the dissolution of active oxides such as active SiO2 and Al2O3 is increased, the surface free energy is increased, the reaction activity is improved, and the secondary hydration reaction process of the composite mineral admixture and calcium hydroxide is accelerated, which not only improves the early and late strength of cement, but also improves the volume stability and durability of cement.
[0025] 3. The carboxyl groups of the methacrylic acid side chains in the methacrylic acid-cellulose copolymer of the present invention interact with cement, and cellulose provides a steric hindrance effect. The hydrophilic hydroxyl groups contained therein can form a water film with a dispersing effect near the cement particles. The composite grinding aid of the specific composition of the present invention can improve fluidity and adhesion, increase production efficiency, shorten grinding time, and reduce product fineness. The composite activator of the specific composition of the present invention can accelerate the hydration rate and improve the overall performance of cement early and late strength. DETAILED DESCRIPTION
[0026] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0027] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0028] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0029] Example 1
[0030] A composite mineral admixture based on iron ore tailings comprises the following raw materials in parts by weight: 35 parts of activated iron ore tailings, 8 parts of layered ultrafine powder, 8 parts of methacrylic acid-cellulose copolymer, 6 parts of limestone powder, 2 parts of composite grinding aids and 2 parts of composite activators.
[0031] The composite grinding aid is polyvinyl alcohol, triethanolamine and calcium sulfate in a mass ratio of 1:4:2.
[0032] The composite activator is nano calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 1:2.
[0033] The layered ultrafine powder is obtained by co-ball milling a mixture of montmorillonite, hydrotalcite and pyrophyllite in a mass ratio of 4:2:1 and a titanate coupling agent (the mass ratio of the mixture of montmorillonite, hydrotalcite and pyrophyllite to the titanate coupling agent is 1:0.2), and the particle size is 5 μm.
[0034] The preparation steps of activated iron ore tailings are as follows: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding to a particle size of 20 μm, and calcining in stages, specifically: first, raising the temperature to 500°C at a heating rate of 2°C / min for calcination for 50 minutes, then raising the temperature to 900°C at a heating rate of 1°C / min for calcination for 45 minutes, and then adding the calcined product to an activation solution (polyvinyl alcohol and acetic acid in a mass ratio of 0.3:1), treating with ultrasound (200 rpm, 50°C) for 1.5 hours, washing and drying to obtain activated iron ore tailings.
[0035] The preparation steps of methacrylic acid-cellulose copolymer are as follows: according to the solid-liquid ratio of 1:15 g / mL, cellulose is added into water and microwave heating (450 W, 70°C) is carried out with stirring for 45 min, ammonium sulfate and methacrylic acid (the molar ratio of ammonium sulfate, methacrylic acid and cellulose is 0.09:1.5:4) are added in sequence and the reaction is carried out for 6 h, sodium hydroxide with a concentration of 0.35 mol / L is added dropwise, and the pH is adjusted to neutral to obtain methacrylic acid-cellulose copolymer.
[0036] The preparation method of the composite mineral admixture based on iron ore tailings comprises the following specific steps:
[0037] (1) The activated iron ore tailings were crushed and ground to a particle size of 25 μm, and layered ultrafine powder and a composite grinding aid with a formula weight of 35% were added, and the grinding was continued until the specific surface area was 500 m 2 / kg;
[0038] (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid is added, and the mixture is ground to a specific surface area of 800 m 2 / kg;
[0039] (3) Mix step (2) and the composite activator evenly and grind until the specific surface area is 1050m 2 / kg, particle size 3μm, to obtain the target composite mineral admixture.
[0040] Example 2
[0041] A composite mineral admixture based on iron ore tailings comprises the following raw materials in parts by weight: 30 parts of activated iron ore tailings, 5 parts of layered ultrafine powder, 5 parts of methacrylic acid-cellulose copolymer, 5 parts of limestone powder, 1 part of composite grinding aid and 1 part of composite activator.
[0042] The composite grinding aid is polyvinyl alcohol, triethanolamine and calcium sulfate in a mass ratio of 1:3:1;
[0043] The composite activator is nano calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 1:1;
[0044] The layered ultrafine powder is obtained by co-ball milling a mixture of montmorillonite, hydrotalcite and pyrophyllite in a mass ratio of 3:1:1 and a titanate coupling agent (the mass ratio of the mixture of montmorillonite, hydrotalcite and pyrophyllite to the titanate coupling agent is 1:0.1), and the particle size is 1 μm;
[0045] The preparation steps of activated iron ore tailings are as follows: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding to a particle size of 15 μm, and calcining in stages, specifically: first, raising the temperature to 400°C at a heating rate of 2°C / min for calcining for 40 minutes, then raising the temperature to 800°C at a heating rate of 1°C / min for calcining for 30 minutes, and then adding the calcined product to an activation solution (polyvinyl alcohol and acetic acid in a mass ratio of 0.2:1), treating with ultrasound (100 rpm, 40°C) for 1 hour, washing and drying to obtain activated iron ore tailings.
[0046] The preparation steps of methacrylic acid-cellulose copolymer are as follows: according to a solid-liquid ratio of 1:10 g / mL, cellulose is added into water for microwave heating (400 W, 60°C) and stirring for 30 min, ammonium sulfate and methacrylic acid (the molar ratio of ammonium sulfate, methacrylic acid and cellulose is 0.08:1:3) are added in sequence for reaction for 5 h, sodium hydroxide with a concentration of 0.3 mol / L is added dropwise, and the pH is adjusted to neutral to obtain methacrylic acid-cellulose copolymer.
[0047] The preparation method of the composite mineral admixture based on iron ore tailings comprises the following specific steps:
[0048] (1) Grind the activated iron ore tailings to a particle size of 20 μm, add layered ultrafine powder and 30% of the composite grinding aid, and continue grinding until the specific surface area is 400 m 2 / kg;
[0049] (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid is added, and the mixture is ground to a specific surface area of 700 m 2 / kg;
[0050] (3) Mix the mixture from step (2) and the composite activator evenly and grind until the specific surface area is 1000 m 2 / kg, particle size 1μm, to obtain the target composite mineral admixture.
[0051] Example 3
[0052] A composite mineral admixture based on iron ore tailings comprises the following raw materials in parts by weight: 40 parts of activated iron ore tailings, 10 parts of layered ultrafine powder, 10 parts of methacrylic acid-cellulose copolymer, 7 parts of limestone powder, 3 parts of composite grinding aid and 3 parts of composite activator.
[0053] The composite grinding aid is polyvinyl alcohol, triethanolamine and calcium sulfate in a mass ratio of 1:5:3;
[0054] The composite activator is nano calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 1:3;
[0055] The layered ultrafine powder is obtained by co-milling a mixture of montmorillonite, hydrotalcite and pyrophyllite in a mass ratio of 5:3:3 and a titanate coupling agent (the mass ratio of the mixture of montmorillonite, hydrotalcite and pyrophyllite to the titanate coupling agent is 1:0.3), and the particle size is 10 μm;
[0056] The preparation steps of activated iron ore tailings are as follows: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding to a particle size of 25 μm, and calcining in stages, specifically: first, raising the temperature to 600°C at a heating rate of 2°C / min for calcining for 60 minutes, then raising the temperature to 1000°C at a heating rate of 1°C / min for calcining for 60 minutes, and then adding the calcined product to an activation solution (polyvinyl alcohol and acetic acid in a mass ratio of 0.4:1), treating with ultrasound (300rpm, 60°C) for 2 hours, washing and drying to obtain activated iron ore tailings.
[0057] The preparation steps of methacrylic acid-cellulose copolymer are as follows: according to the solid-liquid ratio of 1:20 g / mL, cellulose is added into water for microwave heating (500 W, 80°C) and stirring for 60 min, ammonium sulfate and methacrylic acid (the molar ratio of ammonium sulfate, methacrylic acid and cellulose is 0.1:2:5) are added in sequence for reaction for 7 h, sodium hydroxide with a concentration of 0.4 mol / L is added dropwise, and the pH is adjusted to neutral to obtain methacrylic acid-cellulose copolymer.
[0058] The preparation method of the composite mineral admixture based on iron ore tailings comprises the following specific steps:
[0059] (1) Grind the activated iron ore tailings to a particle size of 30 μm, add layered ultrafine powder and 40% of the composite grinding aid, and continue grinding until the specific surface area is 600 m 2 / kg;
[0060] (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid is added, and the mixture is ground to a specific surface area of 900 m 2 / kg;
[0061] (3) Mix the mixture from step (2) and the composite activator evenly and grind until the specific surface area is 1100 m 2 / kg, particle size 5μm, to obtain the target composite mineral admixture.
[0062] Comparative Example 1
[0063] The difference from Example 1 is that the amount of raw materials is different, and the rest is consistent with Example 1.
[0064] The composite mineral admixture based on iron ore tailings in this comparative example includes the following raw materials in parts by weight: 28 parts of activated iron ore tailings, 11 parts of layered ultrafine powder, 4 parts of methacrylic acid-cellulose copolymer, 8 parts of limestone powder, 1 part of composite grinding aid, and 1 part of composite activator.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that the iron ore tailings are not activated, and the rest is the same as Example 1.
[0067] The preparation steps of the iron ore tailings in this comparative example are: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding to a particle size of 20 μm, and calcining in stages, specifically: first raising the temperature to 250°C at a heating rate of 2°C / min and calcining for 50 minutes, then raising the temperature to 500°C at a heating rate of 1°C / min and calcining for 45 minutes to obtain the iron ore tailings.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that the layered ultrafine powder contains only montmorillonite, and the rest is the same as Example 1.
[0070] Comparative Example 4
[0071] The difference from Example 1 is that the methacrylic acid-cellulose copolymer is missing, and the missing raw materials are allocated to other components according to proportion. The rest is the same as Example 1.
[0072] Comparative Example 5
[0073] The difference from Example 1 is that the components in the composite grinding aid lack triethanolamine, and the missing components are distributed to the remaining components according to the proportion. The rest is consistent with Example 1.
[0074] Comparative Example 6
[0075] The difference from Example 1 is that the composite activator contains nano-calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 2:1, and the rest is consistent with Example 1.
[0076] Comparative Example 7
[0077] The difference from Example 1 is that in the preparation step of activated iron ore tailings, the staged calcination is replaced by a single calcination, and the rest is consistent with Example 1.
[0078] The preparation steps of the activated iron ore tailings in this comparative example are as follows: the iron ore tailings are dried to a moisture content of less than 1.0%, crushed and ground to a particle size of 20 μm, the temperature is raised to 900°C at a heating rate of 2°C / min for calcination for 45 minutes, and then the calcined product is added to an activation solution (polyvinyl alcohol and acetic acid in a mass ratio of 0.3:1), ultrasonically treated (200 rpm, 50°C) for 1.5 hours, washed and dried to obtain the activated iron ore tailings.
[0079] Comparative Example 8
[0080] The difference from Example 1 is that the grinding specific surface area of the target composite mineral admixture is 900m 2 / kg, and the others are consistent with Example 1.
[0081] The preparation method of the composite mineral admixture based on iron ore tailings in this comparative example comprises the following specific steps:
[0082] (1) The activated iron ore tailings were crushed and ground to a particle size of 25 μm, and layered ultrafine powder and a composite grinding aid with a formula weight of 35% were added, and the grinding was continued until the specific surface area was 500 m 2 / kg;
[0083] (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid and composite activator are added, and the mixture is ground to a specific surface area of 900 m 2 / kg, particle size 3μm, to obtain the target composite mineral admixture.
[0084] Test example
[0085] The composite mineral admixtures prepared in Examples 1-3 and Comparative Examples 1-8 were mixed, blended and homogenized with cement clinker. The amount of the composite mineral admixture in cement was 40%. The mixture was ground to obtain a cement product, and the performance of the cement product was tested.
[0086] Among them, the fluidity ratio of cement is determined according to GB / T 2419-2005 "Determination method for fluidity of cement mortar"; the compressive strength and flexural strength of cement are determined according to GB / T 17671-2021 standard "Test method for strength of cement mortar (ISO method)".
[0087] The anti-seepage grades are divided into six levels: P4, P6, P8, P10, P12, and >P12, which respectively indicate that they can withstand hydrostatic pressures of 0.4, 0.6, 0.8, 1.0, and 1.2 MPa without water seepage.
[0088] The test results are shown in Table 1-2.
[0089] Table 1
[0090]
[0091]
[0092] Table 2
[0093]
[0094]
[0095] As can be seen from Table 1-2, the composite mineral admixtures prepared in Examples 1-3 of the present invention can significantly improve the compressive and flexural strengths of cement, improve fluidity, have high activity, and ensure early and late strengths. Each component has a synergistic excitation and promotion effect, and jointly improves the activity of the admixture, resulting in high fluidity. The ultrafine composite mineral admixture is effectively filled in the tiny gaps between the unhydrated cement and the hydration product, thereby improving the density of the cement and improving the anti-seepage performance. Compared with Example 1, the various properties of Comparative Examples 1-8 are reduced to varying degrees.
[0096] Leaching toxicity test
[0097] According to GB / T 30810-2014 Determination of Leachable Heavy Metals in Cement Mortar, the leaching toxicity of lead, chromium, cadmium, copper, nickel and barium was determined by flameless atomic absorption spectrophotometry. The detection limits of lead, chromium, cadmium, copper, nickel and barium are 0.005mg / 1 for lead, 0.01mg / 1 for chromium, 0.001mg / 1 for cadmium, 0.005mg / 1 for copper, 0.01mg / L for nickel and 0.02mg / L for barium.
[0098] After testing, the heavy metal elements such as lead and cadmium detected in the cement prepared based on the composite mineral admixtures of Examples 1-3 all meet the national standards.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite mineral admixture based on iron ore tailings, characterized in that: The raw materials include the following in parts by weight: 30-40 parts of activated iron ore tailings, 5-10 parts of layered ultrafine powder, 5-10 parts of methacrylic acid-cellulose copolymer, 5-7 parts of limestone powder, 1-3 parts of composite grinding aid and 1-3 parts of composite activator.
2. A composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The particle size of the layered ultrafine powder is 1-10 μm.
3. The composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The layered ultrafine powder is obtained by ball-milling a mixture of montmorillonite, hydrotalcite and pyrophyllite in a mass ratio of 3-5:1-3:1-3 with a titanate coupling agent; The mass ratio of the mixture of montmorillonite, hydrotalcite and pyrophyllite to the titanate coupling agent is 1:0.1-0.
3.
4. The composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The preparation steps of the activated iron ore tailings include: drying the iron ore tailings to a moisture content of less than 1.0%, crushing and grinding, calcining in stages, adding the product into an activation solution, ultrasonic treatment, washing and drying to obtain the activated iron ore tailings.
5. The composite mineral admixture based on iron ore tailings according to claim 4, characterized in that: The total content of Al2O3 and SiO2 in the iron ore tailings is greater than 63%, and the SO3 content is greater than 1.8%; the ground particle size is 15-25μm; the staged calcination is firstly to increase the temperature to 400-600℃ at a heating rate of 2℃ / min for calcination for 40-60min, and then to increase the temperature to 800-1000℃ at a heating rate of 1℃ / min for calcination for 30-60min; the activation solution is composed of polyvinyl alcohol and acetic acid in a mass ratio of 0.2-0.4:1; the ultrasonic treatment is to ultrasonicate for 1-2h at 100-300rpm and 40-60℃.
6. The composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The preparation steps of the methacrylic acid-cellulose copolymer include: adding cellulose into water, heating and stirring with microwave, adding ammonium sulfate and methacrylic acid in sequence to react for 5-7 hours, dropping sodium hydroxide with a concentration of 0.3-0.4 mol / L, adjusting the pH to neutral, and obtaining the methacrylic acid-cellulose copolymer.
7. A composite mineral admixture based on iron ore tailings as claimed in claim 6, characterized in that: The solid-liquid ratio of the cellulose and water is 1:10-20 g / mL; the microwave heating and stirring is heated at 400-500 W and 60-80° C. for 30-60 min; the molar ratio of ammonium sulfate to methacrylic acid and cellulose is 0.08-0.1:1-2:3-5.
8. The composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The composite grinding aid is polyvinyl alcohol, 7, triethanolamine and calcium sulfate in a mass ratio of 1:3-5:1-3.
9. The composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The composite activator is nano calcium carbonate and polycarboxylate superplasticizer powder in a mass ratio of 1:1-3.
10. The method for preparing a composite mineral admixture based on iron ore tailings according to claim 1, characterized in that: The specific steps include: (1) Grind the activated iron ore tailings to a particle size of 20-30 μm, add layered ultrafine powder and 30%-40% of composite grinding aid, and continue grinding until the specific surface area is 400-600 m 2 / kg; (2) In step (1), methyl methacrylate-cellulose copolymer and limestone powder are continuously added, and the remaining amount of composite grinding aid is added, and the mixture is ground to a specific surface area of 700-900 m 2 / kg; (3) Mix the mixture from step (2) and the composite activator evenly and grind until the specific surface area is 1000-1100m 2 / kg, particle size 1-5μm, to obtain the target composite mineral admixture.
Citation Information
Cited By
Lithium slag-based functional powder as well as preparation method and application thereof
CN120581579A